Langerhans cell histiocytosis of vulva in adolescent. Issue 2 (1st February 2007) - Mottl, H.; Rob, L.; Stary, J.; Kodet, R.; Drahokoupilova, E.
Abstract : Langerhans cell histiocytosis (LCH) affecting child vulva alone is a very rare disease. Only 13 cases of primary vulvar LCH have been previously reported in the medical literature. We describe an additional case in which the LCH was confined to the vulva, with review of the literature. A 16.5-year-old girl presented with papulous and ulcerative lesions on her labia majora and minora. The biopsy revealed a typical histopathologic finding consistent with LCH. A metastatic work-up did not reveal any evidence of the disease except on the vulva. Treatment was carried out according to LCH II protocol. The patient was diagnosed with a recurrent disorder in the vulva 8 months after the completion of primary chemotherapy. For this reason, she underwent second line treatment with 2-chlorodeoxyadenosine. Eighteen months after the second line chemotherapy, the patient has no signs of a local or systemic recurrence. Primary LCH of vulva is very unusual, but we have to keep in mind this possibility when an adolescent girl presents with an atypical chronic lesion on the vulva. This patient appears to be the first case of adolescent 16.5 year old having a solely cutaneous lesion of the vulva